STEMI-Äquivalente im EKG – eine fallbasierte Darstellung - Beckenbauer, Dominik; Martínez Pereyra, Valeria; Ong, Peter (DMW - Deutsche Medizinische Wochenschrift, 2020)
The 12-lead resting ECG remains an indispensable diagnostic tool in patients with acute chest pain. This is particularly important as the identification of ST-segment elevations leads to the diagnosis of ST-segment elevation myocardial infarction (STEMI) and subsequent, immediate coronary reperfusion (usually via primary PCI). However, correct interpretation of the 12-lead ECG in patients with acute chest pain remains challenging. Apart from “classical” ST-segment elevations there are several “equivalents” in the ECG pointing towards an acute coronary occlusion. Among these, hyperacute T-waves, subtle ST-segment elevations, ST-segment elevation in leads aVR/V1 with concomitant ST-segment depression in ≥ 8 other leads and high R-peak with positive T-waves combined with horizontal ST-segment depression in leads V1/V2 can be found. This article provides a case-based presentation of STEMI equivalents on the ECG in order to improve correct ECG interpretation and prognosis of such patients.
Keywords: Myokardinfarkt; STEMI; EKG; Interpretation